La falsación empírica y los problemas lacunae - Islas Mondragón, Damián (2015)
I explore the nature of lacunae problems from the analysis of the concepts of Larry Laudan, Theo Kuipers and Atocha Aliseda, respectively, on the matter. I will suggest that lacunae problems may arise from the weakening of the notion of ‘empirical failure’ and to have repercussions on the notion of ‘logical entailment’.